An efficient flame retardant for silicone rubber: Preparation and application. (November 2015) - Zhu, Chen; Deng, Cong; Cao, Jing-Yu; Wang, Yu-Zhong
Abstract: An efficient flame retardant poly[N, N, N′, N′, N″, N″-hexakis-cyclotriphosphazene-[1, 3, 5]triazine- 2, 4, 6-triamine] (HPTT) was synthesized in this work, and used to flame retard silicone rubber (SR). The flame retardancy of SR/HPTT was investigated by limiting oxygen index (LOI), vertical burning test (UL-94), and cone calorimetry. At 18 wt% HPTT, the SR/HPTT composite achieved a LOI value of 31.8% and UL-94 V-0 rating, and the heat release rate (HRR), the peak of heat release rate (PHRR), and smoke production rate (SPR) were significantly reduced compared those of (neat) SR. All the flame retardation tests indicate that the flame retardancy of SR was greatly improved after incorporating 18 wt% HPTT. The flame-retardant mechanism of HPTT was investigated by thermogravimetric analysis (TGA), scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS). TGA results showed the residue of SR/HPTT was much higher than that of SR. SEM observation showed that the inner residue of SR/HPTT was more compact than that of SR. XPS further demonstrated that the Si–C, C–C, etc. structures were formed in the residue of SR/HPTT. The compact and stable char layer formed at the inner layer of the residue during thermal decomposition must be the leading reason for the excellent flame retardancy of SR/HPTT.